Comparison of Irrigation Water Quality Between Inland and Coastland Areas for Rice Cultivation - Dengiz, O.; Ozturk, E.; Yakupoglu, T. (Asian Journal of Chemistry, 2010)
The main objectives of this study are first to determine and to compare quality of irrigation water sources in between inland and coastland rice fields, second to give some suggestions in order to reduce adversely effect of poor irrigation water quality on the environment and on rice yield. This study was carried out in Cankiri-Kizilirmak district (inland) and Samsun-Bafra delta plain (coastland). Both of them are located on Kizilirmak Basin. For this purpose, total of 19 water samples including 8 surfaces and 11 ground waters were collected from the study areas. Global positioning system (GPS) was used to determine to coordinates of sampling points. To evaluate irrigation water quality, EC, pH, cations (Na+, K+, Ca2+, Mg2+), boron, anions (Cl–, HCO3–, CO32-, SO42-), TDS and SAR were determined by spectrometric, colorimetric and volumetric methods. According to laboratory analysis results, all of the water samples had moderate alkaline reaction, class IV salinity except for SB-1, SB-2 and GB-5 (C3S1) in Bafra region and class II alkalinity (C4S2) except for GB-6, SK-1, GK-4. On the other hand, TDS, boron, total anions or cations concentration were found significantly different each other. These results show that the water in both of the areas is probably going to be affected by local conditions. Due to poor irrigation water quality, irrigation efficiency of the research areas should be incre-ased, improve drainage system and use better genotypes/varieties with tolerance to salinity to reduce high salinity problems and increase further rice productivity.